Multi sensor integration and fussion for a biologically inspired multi-legged robot - 335015 Adly Farriz Faizal (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia/ATMA, 1999